A study on the droplet dynamic behavior on the moving flat plate in the presence of the upper flat tip. (12th October 2017) - Kim, Hyung Rak; Ha, Man Yeong
Highlights: The droplet that has been maintaining the shape at static state. After the influence of the tip, the dynamic contact angle is small. The droplet reaches steady state after the droplet escapes. Abstract: This study carries out three-dimensional numerical simulation using the lattice Boltzmann method to investigate the dynamic behavior of the water meniscus formed between a moving flat bottom wall and a flat tip surface. The effects of the initial droplet contact angle of the bottom wall and upper tip surface, the moving velocity of the bottom wall on the dynamic behavior of the droplet are considered in this study. Under the influence of these parameters considered, the present results show the change in the shape of droplet as a function of time when the droplet is moving in between the bottom wall and the upper tip surface, and also when the droplet is moving along the bottom wall after the droplet completely escapes from the influence of the upper tip surface. This study also shows the variation of the dynamic contact angle of droplet as well as the dimensionless wet lengths between the droplet and the bottom wall or the flat tip as a function of time.